Incidence of medically attended influenza and influenza virus infections confirmed by serology in Ningbo City from 2017–2018 to 2019–2020. Issue 3 (5th January 2022) - Xu, Cuiling; Lao, Xuying; Li, Hongyu; Dong, Libo; Zou, Shumei; Chen, Yi; Gu, Yongquan; Zhu, Yueqin; Xuan, Pingfeng; Huang, Weijuan; Wang, Dayan; Yi, Bo
Abstract: Objectives: In mainland China, the disease burden of influenza is not yet fully understood. Based on population‐based data, we aimed to estimate incidence rates of medically attended influenza and influenza virus infections in Ningbo City. Methods: We used data for outpatient acute respiratory illness (OARI) from a platform covering all health and medical institutes in Yingzhou District, Ningbo City. We applied generalized additive regression models to estimate influenza‐associated excess incidence rate of OARI by age. We recruited local residents aged ≥60 years in the autumn of 2019 and conducted follow‐up nearly 9 months later. Every survey, the sera were collected for testing hemagglutination inhibition antibody. Results: From 2017–2018 to 2019–2020, the annual average of influenza‐associated incidence rate of OARI in all ages was 10.9%. The influenza‐associated incidence rate of OARI was the highest in 2017–2018 (16.9%) and the lowest in 2019–2020 (4.8%). Regularly, influenza‐associated incidence rates of OARI were the highest in children aged 5–14 years (range: 44.1–77.6%) and 0–4 years (range: 8.3–46.6%). The annual average of excess OARI incidence rate in all ages was the highest for influenza B/Yamagata (3.9%). The overall incidence rate of influenza infections indicated by serology in elderly people was 21% during the winter season of 2019–2020. Conclusions: We identified substantial outpatient influenza burden in all ages in Ningbo. Our cohort study limited in elderly people found that this age group had a high risk of seasonal influenza infections. Our study informs the importance of increasing influenza vaccine coverage in high‐risk population including elderly people.